The Effect of Emotion Regulation Training Through Free Expressive Art Therapy on Emerging Adults - Dery Kurniawan; Vania Shavina Santri; Nuning Dewi Lestari; Ivana Nurul Fasha; Umi Latifah (Syntax Corporation Indonesia, 2026)
This study aimed to examine the effect of emotion regulation training using the Free Expressive Art Therapy approach on emotional regulation in young adults. The study employed an experimental design consisting of a control group and an experimental group. Emotional regulation was measured using the Emotion Regulation Questionnaire (ERQ), adapted into the IERQ4S, through pre-test and post-test assessments. The control group participated in a single session of Free Expressive Art Therapy training, while the experimental group received the same training followed by three days of self-guided practice. Data were analyzed using the N-gain test, a normality test, and an independent samples t-test. The normality test indicated that the data were normally distributed (p > 0.05). However, the results of the independent samples t-test showed a significance value of 0.244 (p > 0.05), indicating no statistically significant difference in emotional regulation between the control and experimental groups after the intervention. It can therefore be concluded that emotion regulation training using the Free Expressive Art Therapy approach did not have a significant effect on participants’ emotional regulation. These findings may have been influenced by the relatively short duration of the intervention, participants’ level of engagement, and the nature of emotional regulation itself, which requires a continuous developmental process.